Rebellion Under the Conditions of “Mature Socialism”: The Case of Sigitas Geda - Kmita, Rimantas (Colloquia, 2015)
Drawing on German researcher Angela Borgwardt’s interpretive political theory, the author of this article raises the question of how we should speak about Soviet era writers’ attitudes without making generalizations based on models of resistance/compliance. He analyzes one of the most innovative and rebellious poets of Soviet Lithuania, Sigitas Geda, examining the poet’s attitude during the period of mature socialism and on the eve of the Lithuanian independence movement Sąjūdis.Based on concrete situations and conflicts with the government, the author identifies Geda’s attitude as that of public rebel. Although Geda was not a political dissident, both his creative work and his public attitude represented individual resistance to the system. His poetry generated constant debate, and Geda became famous for his candid character. Like many writers of that older generation, Geda did not belong to the Communist Party, and, although he never engaged in public self-criticism, he was publicly chastised more than once.Geda’s letters and other archival documents reveal that the poet used personal conversations and letters to defend his loyalty to the state and guarantee his legitimacy, and to resolve conflicts with the government and other problems; a more distinct and public compromise was his 1977 play Komunarų gatvė (Communard Street). In his private correspondence, Geda interprets his position and writing as loyal to the Soviet regime and inoffensive to Socialist Realism. Moreover, in defending his position, Geda often went over into attack, and drew on his own well-deserved official status and official aesthetic theory to demonstrate his legitimacy.
Keywords: Soviet literature; attitude; resistance; compliance; Sigitas Geda